Dampak Penerapan Carbon Border Adjusment Mechanism (CBAM) terhadap Ekspor di Indonesia - Hikmah Syahrini; Irnes Febrinabila; Naia Khusnul Nabila; Radhwa Zahirah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The Carbon Border Adjustment Mechanism (CBAM) is a European Union policy instrument designed to equalize carbon costs between domestic and imported products in an effort to prevent carbon leakage and strengthen the transition toward a low-emission economy. This policy has the potential to have significant consequences for developing countries, including Indonesia, which has a carbon-intensive export structure including steel, aluminum, cement, and fertilizers. This research aims to analyze the impact of CBAM implementation on Indonesia's export performance, by examining carbon tariff mechanisms, national industry readiness, economic implications, and issues of fairness in international trade. A qualitative approach was used to examine secondary data from reports by international organizations, policy publications, and academic studies related to CBAM and global trade. The analysis results indicate that CBAM has the potential to reduce the competitiveness of Indonesian products due to increased carbon compliance costs and the industry's dependence on fossil fuels. On the other hand, this policy can be a momentum for Indonesia to strengthen its emissions reporting system, accelerate industrial transformation, and arrange more sustainable trade strategies. The findings of this research are expected to contribute to the development of national policies in the face of the dynamics of international carbon regulations.